Etyka eutanazji. Studium filozoficzno-aksjolingwistyczne - Wawrzyniak, Jan (Wydawnictwo Naukowe UAM, 2016)
The reflections that are presented here focus on the complex issue of how the term ‘euthanasia’ functions in social consciousness. This issue is analyzed from a neonaturalist perspective, which is the theoretical standpoint adopted by the author. The dissertation’s titular term ‘ethics’ is used in a theoretical and meta-ethical sense. A new definition of ‘euthanasia’ as well as a typological evaluation of specific acts is proposed here. The heuristic research aims are as follows: (i) to present the issue while making multithreaded and multi-contextual cultural references from the perspective of analytical philosophy by paying particular attention to the causes of the axiosemantic disorder in contemporary public discourse on the dilemma of euthanasia; (ii) to suggest essential research directions as well as methods of analysis, which could eliminate the inaccuracies and inconsistencies in common conceptual schematizations; and (iii) to point to the possible multiple interpretations of basic concepts and dilemmas. Since in view of the assumptions that are presented here, it is impossible to conduct a purely descriptive narrative study, which would be ideal in meta-axiological terms, the optimal model of a professional discourse on the subject matter is proposed. This model is interdisciplinary as it combines three research perspectives: (i) meta-ethical neonaturalism, (ii) axiolinguistics and analytical ethics, and (iii) area ethics – one of the trends in the applied humanities which proposes specific meta-axiological neutralism. These approaches are interpretative instruments that are used to explain the cultural and historical causes of current axiosemantic chaos as far as the understanding of ‘euthanasia’ is concerned. Given the level of abstraction, or the universal theoretical applicability of the terminology and narration style, this paper is situated within the context of basic research in the humanities and is addressed to experts in the broadly defined field of normative studies, including bioethics.

Rozprawa stanowi analizę zagadnienia eutanazji z uwagi na jego konceptualną obecność w świadomości społecznej, a w jej tytule słowo „etyka” użyte jest nie w moralizatorskim, lecz teoretyczno-metaetycznym sensie. Praca ma charakter interdyscyplinarny, pozostając w kręgu współczesnej normatywistyki, w tym aksjolingwistyki. Narzędziami teoretycznymi są: koncepcja wartości kontrybucyjnej, kategoria transcedentalnego podmiotu wartościowania i decyzji moralnych, pojęcie aksjojęzykowego obrazu świata oraz interpretacji, czyli preferencyjnego tłumaczenia rzeczywistości, a desygnacyjny charakter języka stanowi główny horyzont badawczy. Istotnymi odniesieniami konceptualnymi pozostają też: religijność, godność, tolerancja, jakość i świętość życia oraz kulturowo generowana tzw. naturalność śmierci. Punktem wyjścia jest polisemia i paradoksalność funkcjonowania „eutanazji” we współczesnym uzusie, i swoista demoniczność tego terminu. Aby zidentyfikować przedmiot moralnego sporu, prześledzone zostają kulturowe konteksty aksjosemiotycznych przemian pojmowania eutanazji. Przedmiotem analiz opartych na tekstach źródłowych jest konotacja „eutanazji” przy założeniu, iż samo rozumienie eutanazji i zakres problematyki eutanatologicznej są tworzone sposobami społecznie funkcjonujących narracji tejże problematyki. W pracy – mającej strukturę rozbudowanych esejów powiązanych inkluzywnie – analizowane są pojęcia eutanazji, relatywizmu moralnego, tzw. kultury/cywilizacji śmierci oraz cierpienia. Obecna jest także refleksja, czy na gruncie normatywnej metafizyki chrześcijaństwa eutanazja jest rzeczywiście nieusprawiedliwialna i czy może nawet jest w tej doktrynie od dawna obecna jako jej szczególny akt założycielski. Narracja zmierza – przez aksjometafizyczne fundamenty decyzji eutanastycznych z pozycji abstrakcyjnego panteizmu procesualnego – ku abstrakcyjno-konsensualnej neodefinicji „eutanazji”, nie unikając pozostawienia wątpliwości i pytań otwartych.
Keywords: etyka; eutanazja; relatywizm moralny; cywilizacja; kultura śmierci; wartość; godność; tolerancja; cierpienie; aksjolingwistyka